2015
DOI: 10.1097/rct.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Echo Time T1ρ Is Sensitive to Enzymatic Degeneration of Human Menisci

Abstract: Objective To determine if quantitative ultrashort TE (UTE) T1ρ magnetic resonance (MR) measurements are sensitive to proteoglycan (PG) degradation in human menisci by trypsin digestion. Methods Conventional and quantitative UTE-T1ρ MR sequences were performed on four meniscal samples using a 3T scanner. MR imaging was performed before and after 4, 8, and 12 hours of trypsin solution immersion, inducing PG loss. One sample was utilized as a control. Digest solutions were analyzed for glycosaminoglycan (GAG) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The T1ρ values may reflect changes to the extracellular matrix (ECM), such as proteoglycan (PG) loss. Many in vitro studies have shown that UTE-T1ρ enables the quantitative assessment of short T2 tissues in the musculoskeletal system, and UTE-T1ρ values increase with structural changes in short T2 tissues (14)(15)(16)(17)(18). The magnetization transfer ratio (MTR) provides a measure of the magnetization exchange rate of hydrogen protons bound to macromolecules such as collagen and free water (19).…”
Section: Introductionmentioning
confidence: 99%
“…The T1ρ values may reflect changes to the extracellular matrix (ECM), such as proteoglycan (PG) loss. Many in vitro studies have shown that UTE-T1ρ enables the quantitative assessment of short T2 tissues in the musculoskeletal system, and UTE-T1ρ values increase with structural changes in short T2 tissues (14)(15)(16)(17)(18). The magnetization transfer ratio (MTR) provides a measure of the magnetization exchange rate of hydrogen protons bound to macromolecules such as collagen and free water (19).…”
Section: Introductionmentioning
confidence: 99%